Evaluation of railroad noise: The proximity to railroads and its effect on house prices - Patrick Thiel (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
In 2017, the German federal government passed the Railroad Noise Protection Act to reduce the noise emitted by freight trains. This paper evaluates the effects of this law on house prices by using regional variation comparing affected homes close to train tracks and homes in greater distance before and after the introduction of the national strategy. The difference-in-difference framework suggests an increase in house prices by 0.5% to 2.5% for houses close to the tracks considering different time periods for the act being passed and its complete implementation. A heterogeneity analysis reveals increasing effects with reduced distance to tracks. It also shows that those with the highest general noise burden gain the most from the Railroad Noise Protection Act. – – Im Jahr 2017 verabschiedete die deutsche Bundesregierung das Schienenlärmschutzgesetz zur Reduzierung des von Güterzügen ausgehenden Lärms. In dieser Studie wird die Auswirkung dieser Lärmveränderung untersucht. Dazu werden Preise für betroffene Häuser in der Nähe von Bahngleisen mit Häusern in größerer Entfernung vor und nach der Einführung der nationalen Lärmbekämpfungsstrategie verglichen. Der Differenz-von-Differenzen Ansatz deutet auf einen Anstieg der Hauspreise um 0,5% bis 2,5% für Häuser in Gleisnähe hin, wobei die unterschiedlichen Implementierungsphasen des Gesetzes - die Verabschiedung und die vollständige Umsetzung - berücksichtigt werden. Eine der Heterogenitätsanalysen zeigt, dass die Effektgröße mit abnehmender Distanz zu den Gleisen zunimmt. Weiterhin wird gezeigt, dass diejenigen mit der höchsten allgemeinen Lärmbelastung am meisten von der Einführung des Schienenlärmschutzgesetzes profitieren.
Keywords: O18; Q53; 330; House prices; hedonic price function; railroad noise; Railroad Noise Protection Act